2n-7=5n-10

Simple and best practice solution for 2n-7=5n-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2n-7=5n-10 equation:


Simplifying
2n + -7 = 5n + -10

Reorder the terms:
-7 + 2n = 5n + -10

Reorder the terms:
-7 + 2n = -10 + 5n

Solving
-7 + 2n = -10 + 5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-5n' to each side of the equation.
-7 + 2n + -5n = -10 + 5n + -5n

Combine like terms: 2n + -5n = -3n
-7 + -3n = -10 + 5n + -5n

Combine like terms: 5n + -5n = 0
-7 + -3n = -10 + 0
-7 + -3n = -10

Add '7' to each side of the equation.
-7 + 7 + -3n = -10 + 7

Combine like terms: -7 + 7 = 0
0 + -3n = -10 + 7
-3n = -10 + 7

Combine like terms: -10 + 7 = -3
-3n = -3

Divide each side by '-3'.
n = 1

Simplifying
n = 1

 

See similar equations:

| 9x-7y=11 | | 5-4y+y-1=(-23) | | 3x+12=7(12+x) | | 5m+6=m+18 | | 10p-2(3p-6)=4(3p-6)-8p | | 2x+3=23 | | 5n+7=3n+15 | | 10b-25-3b=1b-1 | | 4x=-44 | | 6y-7=23 | | 33+15w=3w+4w | | -9+4x=-6x+91 | | 9(m-2)=m+10 | | 5x=-7x-12 | | -5x+10=66+3x | | 11x-(2x+7)=5(2x-11) | | -3x-8=7(x+3) | | a+15=53 | | 4x-16=x-7 | | 11+4*2-8= | | 5(2y+3)+5=-10 | | -6x-2y+8+5x-1= | | 11-3(5t-12)=1-(20t+1) | | 15*-6= | | 14a-93=49-57a | | 9x-10x=3 | | 8x=-72 | | 2t-9t+3=6-5t | | 2(x+8)=6x-14 | | -12x-36=-3 | | 125+h=230+7h | | 125+10h=230+7h | | -7p-4(2-4p)=6(p-6)-17 | | 3(n-8)=12+2n | | 10b-25-3b=1b-b | | y=mx+b | | -0.10(64)+0.65x=0.05(x-8) | | 8v=2(4v+2) | | -7=2m+19 | | 2x+5+3x=10 | | 10(v+4)-4v=2(3v+3)-10 | | 10x+25=115 | | -3x+9y=5 | | 7(c+1)-4c=13(3c-2) | | -7x-1=-15 | | w-9w+13=12-5w-4w | | 14-3(5t-12)=1-(t+1) | | 4(t-1)+3=2(t+5) | | 4x+24=4x | | x+9.6=7.8 | | x-2(x+4)=10 | | 5m+6=m+8 | | 2(2x+24)=4x | | -7x-5+4x-3=12x+6-8+2x | | 1.5(4X-1)=-22 | | 4.85=1.25+6.1 | | 3n+5=15 | | 4x+(-4)= | | -5(x+6)+5=10 | | 3=x | | 3=x+3-5x | | 2x-2= | | 2x+12=4x | | 2(2x+12)=4x | | 9x+3-2=5x+7-4 |